PENGAWASAN PARTISIPATIF KAMPANYE DAN MASA TENANG PILKADA SERENTAK 2024 BAGI PELAJAR SMK IBNU TAIMIYAH PEKANBARU - Andrizal, Andrizal; Asnawi, Eddy; Suprayoga, Tatang (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
The partner's problem is that SMK Ibnu Taimiyah Pekanbaru students as new voters in the 2024 simultaneous regional elections who are a strategic part of society do not yet know and understand the importance of participating in election supervision to improve quality. The target of community service activities is to increase knowledge and understanding of the importance of participating in election supervision to improve quality. The solution agreed by the proposing team with partners to overcome priority problems requires socialization in the form of counseling and face-to-face discussions. The method of implementing lectures, delivering materials, on this occasion participants are free to ask questions. The details of this method are, 1. Delivery of materials, 2. Interactive dialogue, this dialogue is a brainstorming session from participants to obtain input in the form of problems, aspirations, proposals, ideas and solutions. Partner participation provides time and mobilizes participants with student status or as target audiences. The output is expected to increase knowledge, understanding of the target audience regarding the importance of participatory supervision of the 2024 simultaneous regional elections, for the proposers the output achieved is in the form of scientific articles.